Impact of Medical Insurance Type on Healthcare Utilization among Older Adults: An Empirical Analysis Based on CHARLS Data - Jiani Chen (Asia Pacific Economic and Management Review, 2026)
Using 2018 CHARLS data, this study examines how medical insurance types affect healthcare utilization among older adults through Logit and negative binomial regression models, along with heterogeneity and robustness tests. The results show a structural interaction between basic and commercial health insurance: commercial insurance promotes outpatient care for Urban Employee Basic Medical Insurance (UEBMI) enrollees but encourages inpatient care for Urban and Rural Resident Basic Medical Insurance (URRBMI) enrollees. Thus, better coordination between basic and commercial insurance is needed to improve the multi-tiered medical insurance system and optimize resource allocation.